An Analysis of Loan Loss Provisioning Behaviour in Chinese Banking from 2012 to 2017 - LU, YUE (2018)
This paper tests the four hypotheses about loan loss provision (LLP), income smoothing, capital management, business cycle and bank efficiency, with the data of 87 commercial banks in China during the period of 2012 to 2017. The empirical results of all these banks support a general procyclicality of loan loss provision and a positive correlation between bank efficiency and LLP. Moreover, there is no evidence for the income smoothing and capital management. However, when excluding state-owned banks, the loan loss provision is counter-cyclical. Also, the manipulation of LLP for the capital regulatory requirement can be found in non- state-owned banks. During the research, in addition to the type classification of banks, recent adjustments of LLP by Chinese government need to be considered as well, especially after the issue of “Capital Rules for Commercial Banks (Provisional)” (CBRC, 2012). Additionally, the special period of time for Chinese banks, high initial public offering (IPO) phase, should also be noted.